Gynecologic Oncology and Inclusion of Women Into the Surgical Workforce: The Canary in This Coal Mine - Hong, Linda J.; Rubinsak, Lisa; Benoit, Michelle F.; Teoh, Deanna; Chandavarkar, Uma; Brockmeyer, Amy; Stevens, Erin; Ioffe, Yevgeniya; Temkin, Sarah M. (Frontiers in Oncology, 2022)
Objective: Women make up a majority of the gynecologic oncology workforce. Increasing the numbers of women in leadership has been proposed as a path towards professional gender equity. This study examined whether leadership gender and departmental infrastructure impact the work environment for women gynecologic oncologists. Methods: Members of a 472-member private Facebook group “Women of Gynecologic Oncology” (WGO) who self-identified women gynecologic oncologists provided demographics, practice infrastructure, personal experience with workplace bullying, gender discrimination, microaggressions using a REDcap survey platform. Results: Of 250 (53%) respondents to this survey, most were younger than age 50 years (93.6%); White (82.2%) and non-Hispanic (94.3%); married (84.7%); and parenting (75.2%). Practice environments included academic (n=152, 61.0%), hospital employed (n=57, 22.9%), and private practice (n=31, 12.4%), and 89.9% supervised trainees. A significant percent of respondents had experienced bullying (52.8%), gender discrimination (57%) and microaggressions (83%). Age, race, ethnicity, practice setting, or mentorship were not statistically significantly associated with these experiences. Reported perpetrators were varied and included colleagues (84%), patients (44%), staff (41%), administrators (18%), and trainees (16%). Rates of bullying (55.0 vs 47.7%, p=0.33), gender discrimination (59.1 vs 52.3%, p=0.33) and microaggressions (83.3 vs 83.0%, p=1.00) were similar irrespective of departmental leadership gender. Conclusions: Women gynecologic oncologists report a high prevalence of workplace bullying, gender discrimination and microaggressions regardless of the gender of their immediate leadership. Proactive and deliberate structural interventions to improve the work environment for surgeons who are women are urgently needed.